Case studies in a passive learning environment: some Malaysian evidence - Nik Ahmad, Nik Nazli; Sulaiman, Maliah (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to explore accounting students’ perceived usefulness of case studies in Malaysia, which has a more passive learning environment, and if gender, prior academic performance and prior exposure to case studies influenced students’ perceptions. Design/methodology/approach – A questionnaire survey on students’ perceived usefulness of case studies based on Weil et al. was used with final-year students enrolled in an advanced management accounting course. The data were gathered over two semesters in 2006/2007. Findings – Findings reveal that generally students felt that the case method was very useful and gave them numerous benefits. However, there were no significant differences in the perceived usefulness of case studies across gender and prior academic performance. Some differences were observed between students with prior exposure to case studies and students without such exposure, in that students without prior exposure perceived higher benefits of case studies. Research limitations/implications – The study showed that students in a passive learning environment generally find case studies to be very beneficial. Practical implications – The case approach should be used more extensively and introduced earlier in accounting undergraduate programmes. Originality/value – This study is one of very few studies which have investigated students’ perceived usefulness of case studies, in a developing country, Malaysia, where a more passive learning environment exists – addressing an important gap in the accounting education literature.